Conservative management of COVID-19 associated hypoxaemia. Issue 2 (6th April 2021) - Voshaar, Thomas; Stais, Patrick; Köhler, Dieter; Dellweg, Dominic
We would like to thank W. Windisch and colleagues for their recognition of our work. Their comments refer to the Early View version of our article, which was immediately uploaded upon acceptance but is not the final, copy-edited version. Unfortunately, there were some technical formatting changes between our submitted version and the version that was uploaded to the ERJ Open Research website. In table 2, for instance, temperature, saturation, respiratory rate, heart rate, and systolic and diastolic blood pressure refer to measurements taken on admission under room air conditions, which explains why the saturation values differ from the nadir oxygen saturation values shown in figure 3. This correspondence argues that happy hypoxaemic patients should not be intubated as long as they remain happy https://bit.ly/3csrpWO